Implementasi Agama dan Perubahan Sosial Masyarakat Minangkabau di Perantauan - Dela Varisa; Lulu Khoirun Nisa; Munifa Husna Haryanti; Muhammad Ghandur (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
This research observes studies on the implementation of religion and social changes of the Minangkabau people overseas. Minangkabau people who migrate are often faced by social changes that are different from their hometowns, including differences in the diversity of religious values and standards for living in a foreign country. This research aims to find out how the Minangkabau people carry out religious teachings and overcome social changes in overseas environments. The approach used is descriptive qualitative . The results of this study show the implementation of the Minangkabau community that continues to carry out religious teaching and carry out social change according to the standards of life overseas, both in their family environment and community. Adaptation of religious teaching becomes a guideline in maintaining the identity and harmony of the Minangkabau tribe that is facing challenges overseas.